Fiqh Muamalah Kontemporer di Maahad Tahfiz Vokasional Aman Bastari Selangor: Tinjauan dari Perspektif Maqāṣid al-Muʿāmalah menurut Ibn ʿĀshūr - Nafisah, Mardiatun; Fathudin (Kartika: Jurnal Studi Keislaman, 2026)
The primary aim is to examine how maqāṣid al-muʿāmalah as articulated by Ibn ʿĀshūr can serve as an evaluative framework to assess alignment between pesantren economic practices and Sharīʿah goals particularly justice, asset protection, contractual clarity, risk mitigation, and equitable benefit distribution. Adopting a qualitative single-case study design, the research draws on in-depth interviews, participant observation, focus group discussions, and analysis of internal documents; data were analyzed thematically to surface recurring patterns and institutional arrangements. Findings indicate a dual pattern: positive measures (e.g., internal asset protection mechanisms, allocation of enterprise profits to social programs, and informal risk-mitigation practices) coexist with shortcomings (contractual ambiguity, limited financial transparency, and uneven profit-sharing). These results highlight a tension between operational flexibility and the demands of maqāṣid-oriented compliance. The study contributes by operationalizing maqāṣid al-muʿāmalah into an analytical tool for institutional assessment and by offering pragmatic recommendations for vocational pesantren and Islamic educational institutions to strengthen governance frameworks that are more transparent, equitable, and welfare-oriented